Cutaneous skeletal hypophosphatemia syndrome: clinical spectrum, natural history, and treatment. Issue 12 (December 2016) - Ovejero, D.; Lim, Y.; Boyce, A.; Gafni, R.; McCarthy, E.; Nguyen, T.; Eichenfield, L.; DeKlotz, C.; Guthrie, L.; Tosi, L.; Thornton, P.; Choate, K.; et al.
Abstract Summary Cutaneous skeletal hypophosphatemia syndrome (CSHS), caused by somaticRAS mutations, features excess fibroblast growth factor-23 (FGF23) and skeletal dysplasia. Records from 56 individuals were reviewed and demonstrated fractures, scoliosis, and non-congenital hypophosphatemia that in some cases were resolved. Phosphate and calcitriol, but not skin lesion removal, were effective at controlling hypophosphatemia. No skeletal malignancies were found. Purpose CSHS is a disorder defined by the association of epidermal and/or melanocytic nevi, a mosaic skeletal dysplasia, and an FGF23-mediated hypophosphatemia. To date, somaticRAS mutations have been identified in all patients whose affected tissue has undergone DNA sequencing. However, the clinical spectrum and treatment are poorly defined in CSHS. The purpose of this study is to determine the spectrum of the phenotype, natural history of the disease, and response to treatment of hypophosphatemia. Methods Five CSHS subjects underwent prospective data collection at clinical research centers. A review of the literature identified 45 reports that included a total of 51 additional patients, in whom the findings were compatible with CSHS. Data on nevi subtypes, bone histology, mineral and skeletal disorders, abnormalities in other tissues, and response to treatment of hypophosphatemia were analyzed. Results Fractures, limb deformities, and scoliosis affected most CSHS subjects. Hypophosphatemia was not present at birth. Histology revealed severe osteomalacia but no other abnormalities. Skeletal dysplasia was reported in all anatomical compartments, though less frequently in the spine; there was no clear correlation between the location of nevi and the skeletal lesions. Phosphate and calcitriol supplementation was the most effective therapy for rickets. Convincing data that nevi removal improved blood phosphate levels was lacking. An age-dependent improvement in mineral abnormalities was observed. A spectrum of extra-osseous/extra-cutaneous manifestations that included both benign and malignant neoplasms was present in many subjects, though osteosarcoma remains unreported. Conclusion An understanding of the spectrum, natural history, and efficacy of treatment of hypophosphatemia in CSHS may improve the care of these patients.